ADAPTASISISTEMPENGHIDUPANMASYARAKATADAT (Studi Kasus Suku Duano Di Desa Concong Luar Kabupaten Indragiri Hilir Provinsi Riau) - Viktor Amrifo (Berkala Perikanan Terubuk, 2012)
This paper explores how the Tribe Community adapted their livelihoodsystem related to socio-ecological changed. Instrumental case study wasconducted to Duano Tribe in Concong Luar Village, Riau Province, Indonesia.“Menongkah” is one of Duano Tribe’s subsistence activity in their livelihoodsystem. The sustainability of this subsistence activity depend on how Duano tribemanage and adapt their livelihood vulnerability. Two tipe of livelihoodvulnerability are ecological vulnerability and social vulnerability.Keywords: Livelihood system, Duano Tribe,vulnerability, social vulnerability